Disiplin Kerja Karyawan Hotel dalam Meningkatkan Pelayanan Tamu Hotel di Hotel Freshfields Taichung - Yolanda Nur Amelia; Didin Syarifuddin (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to examine employee work discipline in improving guest services at Freshfields Hotel Taichung and to identify the challenges encountered in implementing work discipline within the hotel environment. The study employed a descriptive qualitative approach, with data collected through observations, interviews, and documentation involving employees from the front office, housekeeping, and food and beverage service departments. The findings indicate that work discipline plays a significant role in enhancing the quality of hotel guest services. Work discipline is reflected in employees' punctuality, compliance with Standard Operating Procedures (SOPs), sense of responsibility, and professional attitude in serving guests. Strong work discipline contributes to more effective, efficient, and well-organized service delivery, thereby improving guest comfort and satisfaction. However, the study also identified several challenges, including employee tardiness, suboptimal interdepartmental coordination, and inconsistencies in service delivery under certain conditions, all of which may negatively affect service quality. Therefore, regular supervision, discipline evaluation, and continuous service training are essential to ensure the ongoing improvement of hotel service quality.